PENGARUH PRODUK, PERSEPSI HARGA, CITRA MERK, DAN WORD OF MOUTH TERHADAP MINAT BELI PRODUK PRIVATE LABEL GIANT ( STUDI KASUS PADA KONSUMEN GIANT SAWOJAJAR MALANG ) - Qurrotu A'yun; Rois Arifin; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT This research was conducted with the aim of analyzing the Effect of Products, Price Perception, Brand Image, and Word of Mouth on the Interest in Purchasing Giant Private Label Products (Case Study on Giant Sawojajar Malang Consumers. Samples in this research are buyers or consumers of Giant Sawojajar Malang. Analysis Method used is multiple linear regression, based on the results of testing the hypothesis that the results show that there are simultaneous and partial effects of Product variables, Price Perception, Brand Image, and Word of Mouth on the interest in buying Giant Sawojajar Malang Private Label Products. the extent to which the theories obtained during lectures and applied by companies from a practical point of view.